OP0316 Increased expression of microrna-142–3p is associated with the functional defect of regulatory t cells in anti-neutrophil cytoplasmic antibody associated vasculitis. (12th June 2018) - Dekkema, G.; Bijma, T.; Abdulahad, W.; Jellema, P.; Van Den Berg, A.; Kroesen, B.J.; Stegeman, C.; Heeringa, P.; Sanders, J.-S.
Abstract : Background: Circulating regulatory T cells (Tregs) in anti-neutrophil cytoplasmic antibody associated vasculitis (AAV) are frequently functionally deficient. The mechanism behind their impaired function is however unknown. Small non-coding microRNA (miR) are post-transcriptional regulators of protein synthesis and previous studies have shown that differently expressed miRs in T cells are associated with auto immunity. Objectives: To investigate whether the dysfunctionality of Tregs in AAV is due to altered microRNA (miR) expression. Methods: Tregs (CD4 + CD45RO + CD25 + CD127 - ) of healthy controls (HC) and AAV patients in remission without treatment (AAV-REM) were FACS-sorted, and total RNA was isolated. Samples from 8 HCs and 8 AAV-REMs were subjected to miRNA microarray analysis. Based on relative expression and fold change, 5 differentially expressed miRs were validated in an independent cohort using qRT-PCR and a database and literature search was performed to identify potential targets. Results: Nineteen miRs differentially expressed were detected by microarray analysis, of which Let-7g, miR-20a-5p, miR-26a-5p, miR-142–3 p, miR-146a-5p were validated in an independent cohort. Of these, miR-142–3 p was confirmed to be significantly upregulated (2-fold, p=0.03) in Tregs from AAV-REM patients compared to HC Tregs (n=23, n=22). To study the functional impact of miR-142–3 p overexpression, HC Tregs were transfected using either a mimic-miR-142–3 p or a scrambled (SCR)-control. After transfection, live Tregs were co-cultured with T effectors (CD4 + CD25 - ) in a suppression assay to test their suppressive capacity. Transfection with mimic-miR-142–3 p significantly increased the miR-142–3 p levels (2.4 fold, p=0.03) and reduced the suppressive capacity compared to SCR-transduced Tregs (1.9 fold reduction, p=0.02). Moreover, miR-142–3 p levels tended to correlate to the suppressive function of Tregs (p=0.06, rho=−0.591). A database and literature search identified adenylyl cyclase 9 (AC9) as a promising target of miR-142–3 p. mRNA levels of AC9 tended to be lower in AAV-REM patients compared to HC (3.8 fold, p=0.07). In addition, cAMP levels, which are partly produced by AC9, were significantly lower in Tregs from AAV-REM patients after 48 hour of stimulation with anti-CD3 and anti-CD28 (1.7 fold, p=0.003). Conclusions: Increased expression of miR-142–3 p in Tregs of AAV-REM patients is associated with their functional impairment, potentially by targeting the AC9/cAMP mediated suppression. Disclosure of Interest: G. Dekkema: None declared, T. Bijma: None declared, W. Abdulahad Grant/research support from: European Union's Horizon 2020 research and innovation program under grant No 6 68 036., P. Jellema: None declared, A. Van Den Berg: None declared, B. J. Kroesen: None declared, C. Stegeman: None declared, P. Heeringa Grant/research support from: European Union's Horizon 2020 research and innovation program under grant No 6 68 036., J.-S. Sanders Grant/research support from: Nierfonds grant no. 13OKJ39